2018
DOI: 10.3724/sp.j.1041.2018.00997
|View full text |Cite
|
Sign up to set email alerts
|

特质焦虑对急性心理性应激反应的预测 <sup>*</sup>

Abstract: The result showed that the TSST elicited significantly acute psychological stress responses. Specifically, both heart rate and salivary cortisol during the TSST were higher than that measured at any other time points. Regression analysis corroborated that after controlling for gender, age and education years, trait anxiety significantly and negatively predicted heart rate response (β = 0.35, p < 0.01), but not salivary cortisol response to acute psychological stress.The present findings suggest that trait anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…They exhibit low baseline HPA axis response but display a high sympathetic and adrenomedullary responses to acute threats (66)(67)(68). In our study, a blunted response to acute stressors in high trait anxiety participants is consistent with a "dove-like" phenotype (68,69).…”
Section: Recognizing Individuals With High Trait Anxietysupporting
confidence: 70%
“…They exhibit low baseline HPA axis response but display a high sympathetic and adrenomedullary responses to acute threats (66)(67)(68). In our study, a blunted response to acute stressors in high trait anxiety participants is consistent with a "dove-like" phenotype (68,69).…”
Section: Recognizing Individuals With High Trait Anxietysupporting
confidence: 70%
“…Theoretically, both arousal and attention can result in time distortion. Previous studies have found that anxiety would massively increase arousal when negative stimuli appear, such as increased heart rate (Shalom et al, 2015;Peng et al, 2018), increased systolic blood pressure (James et al, 1986;Matthews et al, 1986), reduced heart rate variability (Chalmers et al, 2014), excessive blushing (Gerlach et al, 2001), and increased self-report arousal (Martin, 1961;McLeod et al, 1986). Anxiety has also been found to show an abnormally large attentional bias toward negative stimuli (Bar-Haim et al, 2007), makes individual attracted by negative stimuli and difficult to distract attention from them (Yiend and Mathews, 2001;Koster et al, 2004;Pergamin-Hight et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Pearson correlation analysis indicated that the lower the level of trait anxiety, the higher the level of mental resilience. Previous research also suggested that special factors, such as anxiety, can promote mental well-being (Johnson et al, 2017; Peng et al, 2018; Zhang, 2000). Thus, trait anxiety plays a pivotal role in determining whether athletes can deliver their peak athletic performance in the environment of competitions (Hosseini and Besharat, 2010).…”
Section: Discussionmentioning
confidence: 98%